Different cytokine patterns associate with melancholia severity among inpatients with major depressive disorder - Lucas Primo de Carvalho Alves; Neusa Sica da Rocha (SAGE Publishing, 2020)
Background Six melancholic features (MFs) of the Hamilton Depression Rating Scale (HAM-D 6 ) represent the construct of melancholia along a continuum of severity (from least to most severe: depressed mood, work and activities, somatic symptoms, psychic anxiety, guilty feelings, psychomotor retardation). We aimed to evaluate the association between these MFs and inflammatory cytokines (IC) in the blood. Methods Each IC [interferon gamma (IFN-γ), tumor necrosis factor alpha (TNF-α), interleukin 2 (IL-2), IL-4, IL-6, IL-10, and IL-17] was associated with the HAM-D 6 MFs of 139 severely depressed inpatients, using multiple linear regressions adjusted for covariates. Levels were compared with those of 100 healthy controls. Results Depressed mood was associated with higher levels of IL-4 ( β  = 0.167; p  = 0.041). Psychic anxiety: lower IL-17 levels ( β  = -0.173; p  = 0.039). Guilt feelings: lower IL-2 levels ( β  = −0.168; p  = 0.041) Psychomotor retardation: higher IL-6 levels ( β  = 0.195; p  = 0.017). Depressed patients' TNF-α, INF-γ, and IL-4 levels were not significantly different from controls. Depressed patients' IL-2, IL-6, IL-10, and IL-17 levels were higher than those of controls ( p  <0.001). Conclusion Less severe MFs (depressed mood, psychic anxiety, and guilt feelings) were associated with an anti-inflammatory pattern (higher IL-4, lower IL-17 and lower IL-2, respectively). The presence of the most severe MF, psychomotor retardation, was associated with a higher pro-inflammatory response (higher IL-6).